SI 열화학싸이클 황산분해공정의 Bench-scale 상압 실험 - 전동근; 이기용; 김홍곤; 김창수 (한국수소및신에너지학회, 2011)
The sulfur-iodine (SI) thermochemical water splitting cycle is one of promising hydrogen production methods from water using high-temperature heat generated from a high temperature gas-cooled nuclear reactor (HTGR). The SI cycle consists of three main units, such as Bunsen reaction, HI decomposition, and H_2SO_4decomposition. The feasibility of continuous operation of a series of subunits for H_2SO_4 decomposition was investigated with a bench-scale facility working at ambient pressure. It showed stable and reproducible H_2SO_4decomposition by steadily producing SO_2 and O_2 corresponding to a capacity of 1 mol/h H_2 for 24 hrs.